2017
DOI: 10.18632/oncotarget.23412
|View full text |Cite
|
Sign up to set email alerts
|

Monoclonal gammopathy of renal significance (MGRS) increases the risk for progression to multiple myeloma: an observational study of 2935 MGUS patients

Abstract: PurposeMonoclonal gammopathy of undetermined significance (MGUS) is a premalignancy preceding multiple myeloma (MM) or related disorders. In MGUS, renal impairment caused by deposition of the monoclonal immunoglobulins or free light-chains monoclonal gammopathy of renal significance (MGRS) is often associated with high morbidity and mortality. We analysed the prevalence of renal impairment, clinical features and the long-term outcome in 2935 patients with MGUS.MethodsBetween 1/2000 and 8/2016, 2935 adult patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
45
0
22

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(67 citation statements)
references
References 30 publications
0
45
0
22
Order By: Relevance
“…We reported three cases of progression: one to MM, one to systemic amyloidosis and one to systemic LCDD. A recent study addressed this aspect and showed a risk of progression to MM of 30.6/1000 patients/year in MGRS vs 8.8 in MGUS. Based on these results, follow‐up of these patients is recommended from the haematological and nephrological points of view.…”
Section: Discussionmentioning
confidence: 99%
“…We reported three cases of progression: one to MM, one to systemic amyloidosis and one to systemic LCDD. A recent study addressed this aspect and showed a risk of progression to MM of 30.6/1000 patients/year in MGRS vs 8.8 in MGUS. Based on these results, follow‐up of these patients is recommended from the haematological and nephrological points of view.…”
Section: Discussionmentioning
confidence: 99%
“…Кроме того, при наличии МГРЗ риск прогрессии клона в злокачественный выше, а значит, хуже прогноз в отношении продолжительности жизни. Так, риск трансформации клона в злокачественную форму при МГРЗ в 3,3 раза выше и в течение первого года составляет 10 % [11], что сопоставимо с частотой прогрессирования тлеющей ММ в симптоматическую [34]. Figure 3.…”
Section: прогнозunclassified
“…При этом МГРЗ была выявлена у 4 % пациентов [4]. Эти цифры соотносятся с данными, представленными в мировой литературе [11,28]. По данным Министерства здравоох-ранения РФ, заболеваемость «Гломерулярными, тубулоинтерстициальными болезнями почек, другими болезнями почек и мочеточника» в 2017 году составила 255 случаев на 100 000 взрослого населения.…”
Section: понятие о моноклональной гаммапатии ренального значенияunclassified
“…Кроме того, при наличии МГРЗ риск прогрессии клона в злокачественный выше, а значит, хуже прогноз в отношении продолжительности жизни. Так, риск трансформации клона в злокачественную форму при МГРЗ в 3,3 раза выше и в течение первого года составляет 10 % [11], что сопоставимо с частотой прогрессирования тлеющей ММ в симптоматическую [34].…”
Section: понятие о моноклональной гаммапатии ренального значенияunclassified
See 1 more Smart Citation